2016
DOI: 10.1097/txd.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Alloantigen-Specific Regulatory CD4 T Cell Development and Tissue Distribution After Donor-Specific Transfusion and Costimulatory Blockade

Abstract: BackgroundThe influence of donor-side regulation toward recipient antigens on graft outcome is poorly understood.MethodsBecause this influence might be due in part to the accumulation of tissue-resident memory T cells in the donor organ, we used a standard murine tolerization model (donor-specific transfusion plus CD40L blockade) to determine the kinetics of development and peripheralization of allospecific regulatory T cell in lymphoid tissues and liver, a secondary lymphoid organ used in transplantation.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Interestingly, this in vivo immune regulation/tolerance was dependent on IL-10, TGF-β and IL-35, thereby suggesting a prominent involvement of various subsets of T regulatory cells (Treg) in the observed peripheral immune hyporesponsiveness by the recipient towards the specific donor. A similar pattern of peripheral immune regulation has previously been described in humans and Rhesus monkey due to tolerance to non-inherited maternal antigens [44], as well as in B6 mice made tolerant by donorspecific transfusion plus costimulation blockade [44,45]. Importantly, while the recipient baboon's recall response to TT/D was significantly reduced in the presence of the islet [1] and Ctrl Ag [2]; n = 1 each).…”
Section: And Esmsupporting
confidence: 74%
“…Interestingly, this in vivo immune regulation/tolerance was dependent on IL-10, TGF-β and IL-35, thereby suggesting a prominent involvement of various subsets of T regulatory cells (Treg) in the observed peripheral immune hyporesponsiveness by the recipient towards the specific donor. A similar pattern of peripheral immune regulation has previously been described in humans and Rhesus monkey due to tolerance to non-inherited maternal antigens [44], as well as in B6 mice made tolerant by donorspecific transfusion plus costimulation blockade [44,45]. Importantly, while the recipient baboon's recall response to TT/D was significantly reduced in the presence of the islet [1] and Ctrl Ag [2]; n = 1 each).…”
Section: And Esmsupporting
confidence: 74%
“…A standard approach for inducing peripheral allograft tolerance in mice is the transfusion of splenocytes from one strain into another, followed by treatment with anti-CD154 monoclonal antibody (mAb) (MR-1). Indefinite allograft survival across major histocompatibility complex (MHC) and minor H mismatches is induced in the first week, yet the full maturation of the alloantigen-specific Treg cell response appears to require an active process lasting 4-5 weeks (Tomita et al, 2016). This process occurs in distinct phases.…”
Section: Introductionmentioning
confidence: 99%
“…However, by day 7, newly arising alloantigen-specific T cells are directed toward anergy rather than a Treg cell fate (Burrell and Bromberg, 2012). By day 14, a mixture of self-specific and allo-specific regulation in spleen and lymph nodes can be detected, and by day 35, the self-reactive component of Treg cell suppression has disappeared, and a purely allo-specific regulation pattern emerges that is stable until at least day 70 (Tomita et al, 2016). Alloantigen-specific T cells were shown by tetramer staining on day 30 to be enriched in Treg cells (Young et al, 2018), and the latter were found to be distributed in both lymphoid and non-lymphoid (e.g., liver) tissue compartments (Tomita et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While all 7 patients in our study developed a response to the donor (DR15)−specific ColV peptide post-transplant, 4/7 also developed regulation of this response by either TGF−β (conventional) and IL−35 (EV−based 21 ) cytokines, or both. The role of IL−35 in regulation was previously reported in monkey, 30 human, 31 and mouse 32 immune tolerance studies. Thus, the present report documents a major EV influence on both antigen presentation (DR15 acquisition from the graft by host DC) and regulatory T function (IL−35 “exokine”) in clinical transplantation.…”
Section: Discussionmentioning
confidence: 55%